KOMPARASI PERFORMA MONITOR RADIASI GAMMA DALAM PEMANTAUAN RADIASI REAL–TIME - Arifianto, Rokhmat; Sulaiman, Robi; Slamet; Parulian Hutabarat, Ricard; Cahya Ciputra, Roni; Dian Indrastomo, Frederikus (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
The National Research and Innovation Agency has a research facility used for research on nuclear materials that have potential radiation hazards that can endanger workers. To reduce the potential radiation hazard, radiation monitoring is carried out routinely by workers. To optimize radiation monitoring, three (3) radiation monitors were developed using 1 (one) scintillation (S) radiation detector and 2 (two) GM detectors (GM and GMT) which can later be installed and monitor radiation in real-time. Testing of the 3 radiation monitors developed was carried out in this study to determine the measurement accuracy of each radiation monitor. The tests carried out were linear regression tests to obtain a conversion model from units of counts per second to units of microsivert per hour. In addition, ANOVA testing was conducted to see if there was a significant difference between the dose rate measurements from the three radiation monitors compared to the calibrated surveymeter. Tukey HSD testing was carried out to test each of the developed radiation monitors and compared with a calibrated surveymeter. The results of linear regression testing between the surveymeter (GS) and the three radiation monitors obtained a coefficient of determination above 0.95. ANOVA testing conducted found that there was a significant difference in the average radiation dose rate measurement results from each radiation monitor. Tukey HSD test results show that only one of the radiation monitors has an average radiation dose rate measurement value that is not significantly different from the average radiation dose rate measurement value of the calibrated surveymeter. Therefore, the GMT radiation monitors that have been developed are radiation monitors that are suitable for use in radiation monitoring at nuclear materials research facilities.